Peran Keluarga dalam Menanamkan Ecoliteracy pada Anak Usia Dini - Nopiana Nopiana (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Ecoliteracy or ecological skills are important aspects in shaping the character of children who care about the environment from an early age. Early childhood is a very potential stage of development to receive basic values ​​of environmental concern. Instilling ecoliteracy in children is not only the responsibility of formal educational institutions, but is also greatly influenced by the role of the family as the first and main learning environment. This literature study aims to examine various scientific findings on the role of the family in instilling ecoliteracy in early childhood. The method used is a literature review of various scientific articles, books, and relevant research reports. The results of the study show that parental involvement in environmental-based activities, family communication patterns, provision of an environmentally friendly home environment, and parental role models greatly contribute to shaping children's ecological awareness. In addition, collaboration between families and educational institutions also strengthens the process of internalizing ecoliteracy values. A consistent and comprehensive approach is needed from the family to create a generation that is aware of and cares about environmental sustainability.